2016
DOI: 10.1177/1757975916635504
|View full text |Cite
|
Sign up to set email alerts
|

Advances in health promotion in Asia-Pacific: promoting health through hospitals

Abstract: Since 1990, the WHO Health Promoting Hospital (HPH) movement has tried to facilitate and support hospitals to assume a core responsibility in health promotion. The Taiwan HPH Network was established in December 2006, and became the largest HPH network in the world in 2013. Compared to Europe where the HPH has been more established, the pace of HPH development has been much more rapid. This rapid development provides an inspiring example for research and health promotion practice. Systematic data and empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…However, research conducted in Taiwan showed that health promotion programs provided by hospitals were associated with good health behavior (Chiou et al, 2014). Another impact of implementing health promoting hospitals was a positive for organizational changes in capacity building for the HPH (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, research conducted in Taiwan showed that health promotion programs provided by hospitals were associated with good health behavior (Chiou et al, 2014). Another impact of implementing health promoting hospitals was a positive for organizational changes in capacity building for the HPH (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…al suggest that a shift in health policy is needed to establish health promotion in the hospital and health services setting as a significant and sustainable movement [2]. A study on HPH in Taiwan credits governmental support of the HPH movement, including increased attention to organizational change, as a major reason Taiwan was able to build and maintain a large HPH network and implement numerous projects [25].…”
Section: Key Features Of the 2020 Standardsmentioning
confidence: 99%
“…En el presente suplemento de Global Health Promotion, cinco trabajos procedentes de Taiwán nos ofrecen el análisis de la experiencia de implementar una transformación integral de las organizaciones para generar entornos que promuevan la salud en escuelas, hospitales, lugares de trabajo y ciudades (1)(2)(3)(4)(5). Hu y Kuo (1) explican el funcionamiento de los proyectos de Taiwán como "Ciudad Saludable," y la creación y las funciones de la Alianza de Taiwán de las Ciudades Saludables.…”
unclassified